Mapping Gender Differences in Cardiovascular Disease and Diabetes Care : A Pilot Assessment of LDL Cholesterol Testing Rates in a California Health Plan - Chloe E. Bird , Allen Fremont (RAND Corporation, 2014)
Cardiovascular disease (CVD) and diabetes contribute significantly to the burden of disease among U.S. women and men. CVD includes both heart disease and other vascular diseases, such as those involving blockages of blood vessels outside the heart. CVD is the leading cause of death for women, as well as for men. When heart disease and stroke are counted separately, heart disease remains the leading cause of death among women, cancer is second, and stroke is third (Centers for Disease Control and Prevention, 2010). More than one in three adult women has some form of CVD (American Heart Association and American Stroke Association, 2013), and, despite typically having later onset of CVD, women spend more years living with CVD than do men (American Heart Association Statistics Committee and Stroke Statistics, 2012). Since 1984, more U.S. women than men have died of CVD (American Heart Association and American Stroke Association, 2013); 26 percent of women over age 45 die within a year of having a recognized heart attack, compared with 19 percent of men (American Heart Association Statistics Committee and Stroke Statistics, 2012). Diabetes is a major cardiovascular risk factor, and it increases risk of CVD more so in women than in men (Roche and Wang, 2013). Thus, high-quality routine care for both CVD and diabetes is at least as relevant to women’s health and survival as it is to men’s.